Peran Zakat dan Wakaf Terhadap Kebijakan Fiskal Dalam Perspektif Ekonomi Makro Islam - Syaeful Millah, Aep (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Fiscal policy has the potential to alter government revenue and expenditure to improve economic conditions. In addition to taxes as fiscal policy instruments, zakat and waqf also play a role in fiscal policy, one of the goals of which is to build the national economy. This study aims to explore the role of zakat and waqf in fiscal policy from an Islamic macroeconomic perspective. This research is a library research, with a combination of philosophical and phenomenological approaches. The philosophical approach is used to examine material objects of philosophy in depth, such as values, principles, and objectives of Islamic macroeconomics, as well as the role of zakat and waqf in fiscal policy. Meanwhile, the library approach is used to examine fiscal policy as reflected in society through poverty data and other matters contained in scientific works, documents, and research results. The results of this study demonstrate that the goal of the Islamic macroeconomic system is to improve the welfare of society, realize the maqasid as sharia (objectives of sharia), and uphold the value of justice. Therefore, the distribution of zakat and waqf must be guided by the guidance of Allah and the Sunnah. This reference gives rise to the concept that zakat and waqf play a significant role in fiscal policy. Zakat and waqf are instruments of fiscal policy. Proper management and empowerment of zakat and waqf by the government and the community in a coordinated manner contribute positively to fiscal policy for the community.